Literature Study: Analysis of the Influence of Entrepreneurial Knowledge on Students' Entrepreneurial Interest - Suhardini, Atika; Hasyim, Hasyim; Hutasuhut, Saidun; Sitanggang, Mutiara Miyagi Putri Resipa; Sitopu, Juliaman (ProBisnis : Jurnal Manajemen, 2024)
One of the efforts that the Indonesian government can undertake to reduce unemployment is by fostering entrepreneurial interest from an early age. However, the low interest in entrepreneurship presents a challenge that needs to be addressed, especially among university students, where graduates are expected to be ready for the workforce. Several factors contribute to the low interest in entrepreneurship, including a lack of self-confidence, laziness, insufficient capital, and most notably, a lack of knowledge about entrepreneurship. Entrepreneurial knowledge is a key element in boosting interest in entrepreneurship, as having a solid understanding of entrepreneurship can enhance self-confidence in starting a business. This study aims to analyze the influence of entrepreneurial knowledge on the entrepreneurial interest of university students. The type of research conducted is a literature review, with data collected through reference searches on the internet. From these searches, 21 relevant references were obtained regarding the influence of entrepreneurial knowledge on students' entrepreneurial interest. Based on the analysis of these 21 references, all of them conclude that entrepreneurial knowledge has an impact on entrepreneurial interest. Therefore, it can be concluded that entrepreneurial knowledge affects the entrepreneurial interest of vocational students